2019
DOI: 10.1101/664367
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The GATA3 X308_Splice breast cancer mutation is a hormone context-dependent oncogenic driver

Abstract: 1As the catalogue of oncogenic driver mutations is expanding, it is becoming clear that alterations 2 in a given gene should not be lumped into one single class, since they might have different functions. The 3 transcription factor GATA3 is a paradigm of this. Here, we address the functions of the most common 4 GATA3 mutation (X308_Splice) which generates a neoprotein that we designate as neoGATA3, associated 5 with good patient prognosis. Based on extensive analyses of molecular and clinical data from 6 appro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Wnt/β-catenin signaling pathway is a modulating factor of mammary gland morphogenesis and cell properties 20 and mediates the increase of GATA3 expression 21 . Consistent with our finding, a previous study indicated WNT/β-catenin signaling as an enriched gene set in GATA3 X308_Splice mutant breast tumor 35 . Cell adhesion molecules (CAMs) was another different gene set between tumor samples.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Wnt/β-catenin signaling pathway is a modulating factor of mammary gland morphogenesis and cell properties 20 and mediates the increase of GATA3 expression 21 . Consistent with our finding, a previous study indicated WNT/β-catenin signaling as an enriched gene set in GATA3 X308_Splice mutant breast tumor 35 . Cell adhesion molecules (CAMs) was another different gene set between tumor samples.…”
Section: Discussionsupporting
confidence: 93%
“…However, non-mutant samples showed better survival than others in ER-positive patients. METABRIC data indicated the prognostic value of GATA3 X308_Splice mutation, as the mutant samples had better survival than wild-type ones both in all patients and ER-positive patients 35 . On the other hand, in samples representing a high expression of GATA3 , mutant patients had longer survival than wild-types, and mutations in the second GATA3 zinc-finger (ZnFn2) was associated with lower survival time than other mutations 36 .…”
Section: Discussionmentioning
confidence: 98%
“…GATA3 binds to the chromatin and plays a the pioneering role in the recruitment of ERα and promotes the abnormal proliferation of cells as well as it strongly correlates with ER expression in BC malignancy [37]. GATA3 functions with FOXA1 and ER to enhance ER-responsive genes in normal and pathological situations [38]. Studies provide evidence of additional ERα-cooperating activity of GATA3, which can mediate with enhancer at ERα regulatory regions and has properties similar to FOXA1 [39,40].…”
Section: Pioneer Factors Involved In Erα Recruitment On the Genomementioning
confidence: 99%